A democratização da gestão escolar no município de Santa Bárbara do Pará a partir do PDE - CASTRO, Maria Rosana de Oliveira (Universidade Federal do Pará, 2011)
This study is on schools management democratization in Santa Bárbara do Pará promoted by PDE. It intended to identify PDEs contributions to school management , based on analyses of actions done at Escola Municipal do Livramento. It presents a discussion on State reform and the new proposal of public management, wich is more flexible and able to adapt itself to the tecnological development and to the new global economy needs, that made the State reform to give more importance to values like effient and qualitative services as well as management culture in the organizations. This work shows the connections between educational system and capitalism, that demanded, because of the agrarian exportation crisis (1920) and the improvement of urban-industrial field, better access to schools, mainly to the cities population, relationing education to development and to economy to solve the crisis. It is possible to observe, trhough the research, that educational public policies, originated from international organizations created new forms of regulation and management in the country, in this context appear Fundescola/PDE proposal of management, that reforces the principals role as a leader. The study verified that educational attendance at Pará and at North Region is centred over the eight first years in school (period called fundamental teaching), revealing a great difference from infantile education (little children) and middle teaching (teenagers) that receive few economic attentions. The discussion, presented, on management modernization focus the importance of autonomy and of the participation in the public school as a way to achieve the desired quality in education. The study revels, too, the impositive character of PDEs proposal that ignores external and internal school community in its formulation, being different and contradictory with the proposal established by brasilian educational laws, despite the speech of people who idealized it to affirm it as a participative and democratic proposal.